Ustilago maydis effector Jsi1 interacts with Topless corepressor, hijacking plant jasmonate/ethylene signaling. Issue 6 (3rd January 2021) - Darino, Martin; Chia, Khong‐Sam; Marques, Joana; Aleksza, David; Soto‐Jiménez, Luz Mayela; Saado, Indira; Uhse, Simon; Borg, Michael; Betz, Ruben; Bindics, Janos; Zienkiewicz, Krzysztof; Feussner, Ivo; et al.
Summary: Ustilago maydis is the causal agent of maize smut disease. During the colonization process, the fungus secretes effector proteins that suppress immune responses and redirect the host metabolism in favor of the pathogen. As effectors play a critical role during plant colonization, their identification and functional characterization are essential to understanding biotrophy and disease. Using biochemical, molecular, and transcriptomic techniques, we performed a functional characterization of the U. maydis effector Jasmonate/Ethylene signaling inducer 1 (Jsi1). Jsi1 interacts with several members of the plant corepressor family Topless/Topless related (TPL/TPR). Jsi1 expression in Zea mays and Arabidopsis thaliana leads to transcriptional induction of the ethylene response factor (ERF) branch of the jasmonate/ethylene (JA/ET) signaling pathway. In A. thaliana, activation of the ERF branch leads to biotrophic susceptibility. Jsi1 likely activates the ERF branch via an EAR (ET‐responsive element binding‐factor‐associated amphiphilic repression) motif, which resembles EAR motifs from plant ERF transcription factors, that interacts with TPL/TPR proteins. EAR‐motif‐containing effector candidates were identified from different fungal species, including Magnaporthe oryzae, Sporisorium scitamineum, and Sporisorium reilianum . Interaction between plant TPL proteins and these effector candidates from biotrophic and hemibiotrophic fungi indicates the convergent evolution of effectors modulating the TPL/TPR corepressor hub.